2002
DOI: 10.1074/jbc.m200328200
|View full text |Cite
|
Sign up to set email alerts
|

c-Raf/MEK/ERK Pathway Controls Protein Kinase C-mediated p70S6K Activation in Adult Cardiac Muscle Cells

Abstract: Hypertrophic cardiac growth is a major compensatory response of the heart to an increased mechanical (hemodynamic) load in the form of either pressure or volume overload. Although this response is initially compensatory, a transition from this state to failure occurs when further growth of the heart is not sufficient to normalize the wall stress and maintain contractile function (1). Therefore, a major research interest in cardiovascular disease is to understand how the increase in hemodynamic load is transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
104
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 76 publications
15
104
1
1
Order By: Relevance
“…We also exclude an effect of SB203580 on forskolin-stimulated S6K1 phosphorylation in FRTL-5 cells. A similar result was also reported in feline cardiomyocytes, where forskolin activates both p38 MAPKs and S6K1 (35). It has also been reported that a high concentration of SB203580 reduced the activity of c-Jun N-terminal kinases (JNKs) in rat ventricular myocytes and in transfected COS-7 cells (36, 37), but JNKs were not activated either by cAMP in FRTL-5 cells (11) or by IGF-I in human thyrocytes (38).…”
Section: Discussionsupporting
confidence: 64%
“…We also exclude an effect of SB203580 on forskolin-stimulated S6K1 phosphorylation in FRTL-5 cells. A similar result was also reported in feline cardiomyocytes, where forskolin activates both p38 MAPKs and S6K1 (35). It has also been reported that a high concentration of SB203580 reduced the activity of c-Jun N-terminal kinases (JNKs) in rat ventricular myocytes and in transfected COS-7 cells (36, 37), but JNKs were not activated either by cAMP in FRTL-5 cells (11) or by IGF-I in human thyrocytes (38).…”
Section: Discussionsupporting
confidence: 64%
“…4B, right panel). The minor inhibition of rpS6 phosphorylation by U1026 probably reflects the cross-talk between ERK/RSK and mTOR/ S6K signaling cascades (55)(56)(57). Interestingly, even a combination of rapamycin and U0126 did not inhibit eIF4B phosphorylation completely (Fig.…”
Section: Orf45 Increases Phosphorylation Of Eif4b and Rps6-wementioning
confidence: 99%
“…Notably, Erk-driven tumorigenesis in TSC2 þ /À tumor cells was shown to be blocked by an Erknonphosphorylatable TSC2 mutant, but reintroduction of wild-type TSC2 was ineffective in suppressing tumor growth (Ma et al, 2005a). It is also worthwhile to note that agonists which activate PKC such as phorbol 12-myristate 13-acetate can also regulate mTOR via PKCmediated activation of Ras and Raf (Iijima et al, 2002;Tee et al, 2003a). Collectively, these findings place the Ras/MAPK pathway -independently of Ras's ability to activate PI3K -upstream of the TSC1/2 complex.…”
Section: Negative and Positive Feedbackmentioning
confidence: 99%